Transitioning to an internet-based mobile service provider a critique on a mobile network operator's technology strategy - Orense, Bethany Lauri C. (University of the Philippines Diliman, 2013)
The goal of mobile communication technology is to be as sophisticated as possible—to a point where technology capabilities, capacities and coverage are so advanced that mobile network operators (MNOs) are barely differentiated by their respective fixed assets or technological infrastructure but by the very business model they follow. As mobile subscribers, we leave it to our mobile service providers to test, perfect and continue innovating mobile technologies and creating even more reliable mobile platforms for us. The most reliable platforms themselves (and even the least reliable ones) subsequently influence our communication behavior and patterns. The technologies and corresponding communication behaviors and patterns have changed so much that the word communication is somehow no longer sufficient to describe the act of communicating. Hence, communication has evolved into what we now know as collaboration and convergence. In the process, we may not even know what we have been missing until a specific platform has been laid down in front of our very eyes. This is called technology push. We likewise passively leave it to MNOs to match our unaddressed needs and preferences, i.e. what mobile services (product) do they tell us (promotion) we can afford (price) at the exact moment (and place) we need them. This is called market matching.